Habitual tea drinking associated with a lower risk of type 2 diabetes in Vietnamese adults - Nguyen, C.; Lee, Andy; Pham, N.; Van Do, V.; Ngu, N.; Tran, B.; Binns, Colin (HEC Press, 2018)
© 2017, HEC Press. Background and Objectives: The association between tea consumption and type 2 diabetes risk remains inconsistent in Asian populations. This case-control study investigated the association between habitual tea consumption and the risk of type 2 diabetes among Vietnamese adults. Methods and Study Design: A hospital-based case-control study was conducted during 2013-2015 in Vietnam. A total of 599 newly diagnosed diabetic cases (aged 40-65 years) and 599 hospital-based controls, frequency matched by age and sex, were recruited. Information about frequency, quantity, and duration of tea drinking, together with demographics, habitual diet and lifestyle characteristics, was obtained from direct interviews using a validated and reliable questionnaire. Unconditional logistic regression analyses were performed to assess the association between different metrics of tea consumption and the type 2 diabetes risk. Results: Control subjects reported higher tea consumption levels than the cases in terms of duration, frequency, and quantity of tea drunk. After accounting for confounding factors, increasing tea consumption was found to be associated with a reduced risk of type 2 diabetes; the adjusted odds ratio (95% confidence interval) was 0.66 (0.49, 0.89) for participants drinking > 2 cups/day, relative to those drinking < 1 cup/day. Significant inverse dose-response relationships were also observed for average number of cups consumed daily and years of tea drinking (p < 0.01). Conclusions: Habitual tea consumption is associated with a reduced risk of type 2 diabetes among Vietnamese adults.